Analisis Siswa Pasif dalam Pembelajaran IPS Kelas VIII di UPT SMP Negeri 2 Kademangan Kabupaten Blitar - Erni Yusnia; Jani Jani (Universitas Palangka Raya, 2024)
Educators are highly respected figures in schools because they have a big role in the success of learning. The focus of research in this thesis is (1) What are the factors that influence passive students in social studies learning in class VIII at SMP Negeri 2 Kademangan, Blitar Regency? (2) What are the teacher's efforts to overcome passive students in class VIII social studies learning at SMP Negeri 2 Kademangan, Blitar Regency? The research objectives of this thesis are (1) To explain the factors that influence passive students in social studies learning in class VIII at SMP Negeri 2 Kademangan, Blitar Regency (2) To explain teachers' efforts in overcoming passive students in class VIII social studies learning in junior high schools. Negeri 2 Kademangan Blitar Regency. This research is research using a descriptive qualitative approach. The results obtained from this research are (1) There are two factors that influence passive students in social studies learning in class VIII at SMP Negeri 2 Kademangan Blitar Regency for the 2023/2024 academic year, the first is external factors, namely the family environment and the school environment. The two internal factors are feeling lazy, feeling sleepy, not liking social studies subjects and students' inadequate nutrition. (2) The teacher's efforts to overcome passive students in class VIII social studies learning at SMP Negeri 2 Kademangan Blitar Regency for the 2023/2024 academic year are the first to motivate students with the class VIII social studies teacher always motivating students, using interesting learning methods. group discussions, giving punishments, developing teaching media.